Diazepam binding inhibitor promotes progenitor proliferation in the postnatal SVZ by reducing GABA signaling - Alfonso, Julieta; Le Magueresse, Corentin; Zuccotti, Annalisa; Khodosevich, Konstantin; Monyer, Hannah (Cell stem cell, 2012)
The subventricular zone (SVZ) of the lateral ventricles is the largest neurogenic niche of the postnatal brain. New SVZ-generated neurons migrate via the rostral migratory stream to the olfactory bulb (OB) where they functionally integrate into preexisting neuronal circuits. Nonsynaptic GABA signaling was previously shown to inhibit SVZ-derived neurogenesis. Here we identify the endogenous protein diazepam binding inhibitor (DBI) as a positive modulator of SVZ postnatal neurogenesis by regulating GABA activity in transit-amplifying cells. We performed DBI loss- and gain-of-function experiments in vivo at the peak of postnatal OB neuron generation in mice and demonstrate that DBI enhances proliferation by preventing SVZ progenitors to exit the cell cycle. Furthermore, we provide evidence that DBI exerts its effect on SVZ progenitors via its octadecaneuropeptide proteolytic product (ODN) by inhibiting GABA-induced currents. Together our data reveal a regulatory mechanism by which DBI counteracts the inhibitory effect of nonsynaptic GABA signaling on subventricular neuronal proliferation.